Discovery Learning-Based E-Book Enhances Elementary School Students’ Critical Thinking Skills - Angga Pradnyana, I Gede Bagus; Lisna Handayani, Ni Nyoman; Adnyana, I Komang Surya (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
Learning is still predominantly conventional, with a high level of dependence on printed textbooks that are limited in quantity. Therefore, this classroom action research was conducted by implementing a discovery learning-based e-book aimed at improving students’ critical thinking skills. The subjects of this study were 30 fifth-grade students of SDN 2 Bongkasa, Badung, Bali. This study employed a classroom action research method conducted in two cycles. The research instrument used was a test of students’ critical thinking skills. The results showed that in Cycle I, the mean score was 74, the median was 75, the mode was 75, and the classical mastery level reached 60%. Therefore, the study was continued to Cycle II. In Cycle II, the mean score increased to 87, the median to 88, the mode to 90, and the classical mastery level improved to 93%. The improvement in classical mastery from Cycle I to Cycle II indicates that the implemented action was successful; therefore, the study was concluded at Cycle II. In conclusion, the discovery learning-based e-book was effective in improving elementary school students’ critical thinking skills. It is recommended that future researchers expand this study by involving a broader range of subjects.